The Significance of Regulating Artificial Intelligence and Cybersecurity for Sustainable Trade - Stanković, Ljiljana; Dimic, Maja; Babić, Violeta; Cvijić, Lazar; Jović-Stanković, Daliborka (Industrija, 2026)
The accelerated digitalization of trade and the growing use of artificial intelligence (AI) offer significant economic benefits but also raise important concerns related to data protection, privacy, and cybersecurity. This paper examines the importance of regulating AI and cybersecurity for the sustainable development of trade, based on the assumption that a stable and coherent regulatory framework is essential for market resilience, consumer trust, and long-term competitiveness. The analysis provides a comparative overview of the regulatory models of the European Union and the Republic of Serbia, focusing on key instruments such as the AI Act, the NIS2 Directive, the GDPR, and relevant national strategies and legislation. The findings show that the EU relies on an integrated approach linking innovation, safety, and consumer rights, while the Serbian framework remains fragmented and in transition. Special attention is devoted to the implications of these regulations for trading companies, business partners, and consumers, as well as to the need for harmonizing national policies with EU standards. The paper concludes that regulating AI and cybersecurity plays a decisive role in building a secure, transparent, and competitive trade ecosystem in the digital economy.